KEJADIAN PNEUMONIA PADA BATITA DI WILAYAH KERJA PUSKESMAS SUKAMERINDU KOTA BENGKULU - Hartini, Lela; Ismiati, Ismiati (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Pneumonia is an infection or inflammation of the lower respiratory tract that involves the alveoli and bronchioles. Risk factors for pneumonia which occurs in boys aged 1-3 years with a skinny body weight. Pneumonia is the leading cause of death of infants and toddlers in Indonesia with a total percentage (23.6%), which is the largest proportion of all-cause mortality in infants and toddlers. This study used a descriptive design, with a population of children aged 1-3 years which amounted to 51 people, technique data sampling was used Total Sampling, data collection secondary techniques, data obtained by existing records in health centers (patient registers). The results showed that the majority (60.8%) children aged 13-24 months, the majority (72.5%) child-sex male, and most (56.9%) children were in the category of lean body weight. It is recommended to parents, especially mothers to be able to take precautions against the occurrence of pneumonia, such as providing adequate nutrition to children so that children are not malnourished which can increase the risk of pneumonia